2009
DOI: 10.1063/1.3147221
|View full text |Cite
|
Sign up to set email alerts
|

A spatial light modulator for terahertz beams

Abstract: We design and implement a multipixel spatial modulator for terahertz beams using active terahertz metamaterials. Our first-generation device consists of a 4×4 pixel array, where each pixel is an array of subwavelength-sized split-ring resonator elements fabricated on a semiconductor substrate, and is independently controlled by applying an external voltage. Through terahertz transmission experiments, we show that the spatial modulator has a uniform modulation depth of around 40% across all pixels, and negligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
175
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(175 citation statements)
references
References 16 publications
0
175
0
Order By: Relevance
“…A good linear relationship between the relative transmission and the control beam intensity is observed within the range from 0 to 100 mJ/cm 2 . Compared with the electrically controlled THz spatial modulator 22 , this optically controlled STM has higher resolution and better modulation depth. To evaluate the resolving power of the STM, a 1951 USAF 1X resolution test chart (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A good linear relationship between the relative transmission and the control beam intensity is observed within the range from 0 to 100 mJ/cm 2 . Compared with the electrically controlled THz spatial modulator 22 , this optically controlled STM has higher resolution and better modulation depth. To evaluate the resolving power of the STM, a 1951 USAF 1X resolution test chart (Fig.…”
mentioning
confidence: 99%
“…al. proposed a multi-pixel spatial modulator for THz beams using active THz metamaterials 22 . The transmission of each unit cell can be independently controlled by applying a small external voltage at room temperature.…”
mentioning
confidence: 99%
“…It is also the first to operate at switching voltage of 1 V, and the lowest reported to-date is 14 V. 15 Unlike current solid-state THz SLMs, the embedded HEMT device in every split-gap allows very high speed operation 19 (∼10 MHz), even GHz operation if designed appropriately. We would like to emphasize that since the imaging is effectively done at a single frequency, a commercial THz imaging system can be designed with a more sensitive single-pixel detector and cheaper source, such as a Schottky diode and diode multipliers, which will be much lower power and cost compared to the cw THz spectrometer used in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated THz SLMs using all-electronic dynamic metamaterials used in single-pixel THz imaging systems. 10,15,16 These dynamic metamaterial SLMs are electronically controlled by injecting charges or depleting them in the bulk semiconductor substrate, which is an inherently slow process due to the intrinsically large capacitance of what is essentially a large bulk diode structure. 15,17,18 This results in a slow switching speed and large dynamic power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Established electronic solutions have high energy requirements and complexity as they require conversion between optical and electronic signals, while all-optical techniques enabled by photorefraction are slow. Recently, several metamaterial-based approaches to dynamic spatial control over optical signals have emerged, [6][7][8] including all-optical ones, 9,10 which create interesting possibilities.…”
mentioning
confidence: 99%